Design and experiment evaluation of furrow compaction device with opener for maize - Wang, Wenjun; Diao, Peisong; Jia, Honglei; Chen, Yulong (International Journal of Agricultural and Biological Engineering, 2020)
The double-disc opener of maize precision seeder is an important component which affects sowing quality. After the double-disc opening operation, there will be many unfavorable phenomena such as a W-shaped bottom with pointed ridge, returning soil to furrow, loose and rough furrow sidewall, and large soil blocks in the furrow bottom. These phenomena often cause the problems of poor sowing depth consistency and seed spacing uniformity. In order to solve the above problems, the furrow compaction device with opener was designed to compact and reshape the original seed furrow, eventually forming a smooth and flat V-shaped seed furrow. Through theoretical calculations and kinematic analysis, the main structural parameters of the device were limited to a small range: the spring stiffness coefficient k=0.96-4.19 N/mm and the angle of the furrow compaction wheel φ=30°-60°. In the soil-bin experiment, the rotary combination design was adopted to study the effects of the parameters of the furrow compaction device with opener on the seeds location variation. The regression model of two factors with respect to each indicator was established in the Design-Expert software, revealing the effects of two factors on the indicators. Finally, the optimal structural parameters obtained were: the spring stiffness coefficient k=4.0 N/mm, and the angle of furrow compaction wheel φ=42.4°. The field test was carried out to verify the effect of the furrow compaction device with opener on the performance of precision seeder. The results showed that the average values of the sowing depth variable coefficient, the lateral deviation and the seed spacing variable coefficient respectively were 5.77%, 5.1 mm and 9.54% in the treatment of the furrow compaction device with opener. All indicators were superior to the traditional double-disc opener. This research can provide references for the design of furrow opening device and maize precision seeder.Keywords: furrow opener, seed furrow, compaction, sowing depth variable coefficient, lateral deviation, seed spacing variable coefficientDOI: 10.25165/j.ijabe.20201302.4941Citation: Wang W J, Diao P S, Jia H L, Chen Y L. Design and experiment evaluation of furrow compaction device with opener for maize. Int J Agric & Biol Eng, 2020; 13(2): 123–131.